The Urgency of Recognition the Rights of Indigenous Peoples in Asymmetric Decentralization in Papua and Papua Barat - Anifa Aprilia Sejati; Drajat Tri Kartono (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2024)
Asymmetric decentralization is a special method given to certain provinces in Indonesia amidst the diversity of cultures, customs and specialties of certain regions. The central government's policy in the form of regional autonomy apparently has an impact on indigenous communities, resulting in frequent conflicts and unclear recognition of customary rights, especially in Tanah Papua. The aim of the research is to determine the importance of recognizing indigenous communities in asymmetric decentralization in Papua and West Papua. The research method used is qualitative, data was obtained by searching the literature and presented with descriptive analysis. The results of this research are that Indonesia does not yet have regulations at the "law" level that recognize the existence and rights of indigenous peoples, especially in Papua and West Papua. One of the government's admissions is that through Asymmetric Decentralization with special autonomy it still causes public dissatisfaction. Therefore, recognition of people's rights through draft laws or "laws" is very important to implement. According to the research, ratifying the Indigenous Peoples Bill is essential for strengthening the legal and policy foundation for indigenous peoples' rights fulfillment.